PELATIHAN PENGELOLAAN PENDANAAN UNTUK IBU-IBU PKH YANG BERDAGANG - Zulkarnain Sulistyo; Mikael Keyshar; Mohammad Teguh; Muhammad Gandung (Abdi Jurnal Publikasi, 2026)
This community service training focuses on financial management for women recipients of the Family Hope Program (PKH) who run small trading businesses. The training aims to improve financial literacy and economic independence of micro-entrepreneurs. Activities focused on understanding basic business financial management, separating personal and business finances, simple cash flow recording, and effective capital planning. Training methods include material delivery, discussion, and direct practice through financial recording simulations. The results showed an increase in participants' understanding in managing business funding in a more orderly and planned manner. This training is expected to help PKH mothers optimize business income, reduce financial risks, and support business sustainability independently.